Privatization and Oligopolies of the Renal Replacement Therapy Sector on Contemporary Capitalism: A Systematic Review and the Brazilian Scenario - Samaan F; Mendes Á; Carnut L (Dove Medical Press, 2024)
Farid Samaan,1,2,* Áquilas Mendes,3,4,* Leonardo Carnut5,* 1Planning and Evaluation Group, São Paulo State Health Department, São Paulo, SP, Brazil; 2Research Division, Dante Pazzanese Cardiology Institute, São Paulo, SP, Brazil; 3Public Health School, University of São Paulo, São Paulo, SP, Brazil; 4Postgraduate Program, Pontifícia Universidade Católica, São Paulo, SP, Brazil; 5Center for the Development of Higher Education in Health, Federal University of São Paulo, São Paulo, SP, Brazil*These authors contributed equally to this workCorrespondence: Farid Samaan, Planning and Evaluation Group, São Paulo State Health Department, Av. Dr. Arnaldo, 351 - 5th Floor, Room 501, São Paulo, SP, 01246-903, Brazil, Tel +55 11 3066-8165, Email fsamaan@saude.sp.gov.brAbstract: Worldwide the assistance on renal replacement therapy (RRT) is carried out mainly by private for-profit services and in a market with increase in mergers and acquisitions. The aim of this study was to conduct an integrative systematic review on privatization and oligopolies in the RRT sector in the context of contemporary capitalism. The inclusion criteria were scientific articles without language restrictions and that addressed the themes of oligopoly or privatization of RRT market. Studies published before 1990 were excluded. The exploratory search for publications was carried out on February 13, 2024 on the Virtual Health Library Regional Portal (VHL). Using the step-by-step of PRISMA flowchart, 34 articles were retrieved, of which 31 addressed the RRT sector in the United States and 26 compared for-profit dialysis units or those belonging to large organizations with non-profit or public ones. The main effects of privatization and oligopolies, evaluated by the studies, were: mortality, hospitalization, use of peritoneal dialysis and registration for kidney transplantation. When considering these outcomes, 19 (73%) articles showed worse results in private units or those belonging to large organizations, six (23%) studies were in favor of privatization or oligopolies and one study was neutral (4%). In summary, most of the articles included in this systematic review showed deleterious effects of oligopolization and privatization of the RRT sector on the patients served. Possible explanations for this result could be the presence of conflicts of interest in the RRT sector and the lack of incentive to implement the chronic kidney disease care line. The predominance of articles from a single nation may suggest that few countries have transparent mechanisms to monitor the quality of care and outcomes of patients on chronic dialysis.Keywords: renal dialysis, chronic kidney failure, health facility merger, private sector, capitalism, review